Processamento e estudo das propriedades de filmes e peças injetadas de nanobiocompósitos de nanocristais de celulose e matrizes biodegradáveis - Morelli, Carolina Lipparelli (Universidade Federal de São Carlos, 2014)
This study aimed at evaluating the potential of application of cellulose nanocrystals as reinforcing elements of biodegradable polymeric matrices, in the films and injection molded pieces applications. Two polymeric matrices with different properties were used, namely: poly(butylene adipate-co-terephthalate), PBAT, and poly(lactic acid), PLA. For the extraction of cellulose nanocrystals (NCC), two sources were selected: microcrystalline cellulose (CMC) and balsa wood . Due to the high polarity of cellulose nanocrystals, different approaches of surface chemical modifications of these particles were tested, in order to ensure their good dispersion when added to polymeric matrices of lower polarity. They were: a) chemical modification with two types of isocyanates, an aliphatic one (octadecyl isocyanate) and an aromatic one (phenylbutyl isocyanate); b) grafting of poly (butylene glutarate) using the in situ polymerization technique; c) silanization treatment; and d) grafting of poly(acrylic acid) through click chemistry technique. Modified and unmodified NCCs were processed with PBAT and PLA by casting or melt extrusion processing techniques. In general, the chemical modification of NCC surface increased their thermal resistance, decreased their polarity and improved their dispersion into PLA and PBAT matrices. Some of these treatments, as well as the processing conditions enabled an increase in the overall mechanical properties of the polymers. Thus, the characterization of the nanocomposites showed that NCC addition increased the elastic modulus of the matrix and retained its higher stiffness even under relatively high temperatures. Higher NCC contents led to larger increases in the stiffness of the ensuing composites. The water vapor permeability of PBAT was also reduced with the introduction of NCC. This work points out several potential good perspectives for the use of celulose nanocrystals as reinforcing elements of polymeric matrices. It showed also that it is possible to obtain significant improvements in the polymer properties using the same processing techniques as those used at industrial scale, such as melt extrusion and injection molding.
Keywords: Polímeros; Nanocristais de celulose; Polímeros biodegradáveis; Nanocompósitos; Modificação química superficial; Processo de extrusão; Moldagem por injeção; Percolação; Celulose nanocrystals; Biodegradable polymers; Nanocomposites; Chemical surface modification; Extrusion; Injection molding; Percolation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA